Determination of Thermal Diffusivity Values Based on the Inverse Problem of Heat Conduction – Numerical Analysis - Adamowicz, Adam (Acta Mechanica et Automatica, 2022)
This paper presents a discussion on the accuracy of the method of determining the thermal diffusivity of solids using the solution of the inverse heat conduction equation. A new measurement data processing procedure was proposed to improve the effectiveness of the method. Using the numerical model, an analysis of the sensitivity of the method of thermal diffusivity determination to changes in operational and environmental parameters of the test was carried out. The obtained results showed that the method was insensitive to the parameters of the thermal excitation impulse, the thickness of the tested sample, and the significant influence of convection cooling on its accuracy. The work was completed with the formulation of general conclusions concerning the conditions for determining the thermal diffusivity of materials with the use of the described method.